PERLINDUNGAN VARIETAS TANAMAN YANG DIHASILKAN OLEH PEMULIA TANAMAN BERDASARKAN UNDANG-UNDANG NOMOR. 29 TAHUN 2000 TENTANG PERLINDUNGAN VARIETAS TANAMAN (PVT) - Luckyani Sidauruk, Rosia; Dunia, Ngakan Ketut; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum, 2014)
IPR (Intellectual Property Rights) is described as property rights are born ashuman intellectual abilities. Indonesia has a biological resource that is a sourceof germplasm and can be used to assemble high-yielding varieties that stronglysupports the future development of the agricultural sector. In connection with therampant piracy of plant varieties that formed the Law No. 29 Year 2000 regardingPlant Variety Protection. This paper aims to explain how to determine theuniformity requirement of a new crop varieties and legal protection of plantbreeders over plant varieties produced in accordance with Law No. 29 of 2000with normative legal research methods in this paper have a conclusion how todetermine the uniformity requirement of a new crop varieties with the petition file,the discovery proves novelty properties, properties of new crop varieties privilegeand legal protection to plant breeders over plant varieties produced are of specialprotection rights.
Keywords: Protection, Haki, Varieties, Plant